A contribution from Voloshinov's philosophy of language to semiotic studies - Villarta-Neder, Marco Antonio; Dias, Fábio Luiz de Castro (Estudos Semióticos, 2023)
This article aim to discuss how Voloshinov's philosophy of language (2017 [1929]) can contribute to semiotic studies, especially in its philosophically sociological character. First, we start with a definition of the historical-epistemological perspective that characterizes our reflection, and we highlight one of the moments in which Voloshinov's philosophy was explicitly present in the work of Juri Lotman [1922 1993], one of the most important semioticians. Second, we characterize the sociologism of 1920s and 1930s in the USSR in which Voloshinov worked scientifically, a factor that greatly contributed to define his philosophy of language as an epistemically sociological stance. Finally, we begin to discuss, after a brief debate on the philosophical primacy of social interaction that is presupposed by that philosophy, how Voloshinov's concept of enunciation (2017 [1929]) can serve as a starting point for a semiotic in a sociological hue. This article aims to contribute to the defense of interdisciplinary logic in the field of language studies. In addition, it is intended to participate in epistemological and historical approach to ideas.